Increasing Pollution with Optimal Corrective Taxes - John M. Hartwick (Queen's University, Department of Economics, 1990)
In a simple two factor, two good, two person general equilibrium model with pollution, we indicated a case in which the introduction of optimal Pigovian corrective taxes results in an equilibrium with a higher level of pollution. Our argument turns on our two persons earning incomes from distinct input sources and having different tastes for the two goods, one of which causes pollution. The introduction of taxes causes one person's income to rise relative to the other person's and can induce a shift in total consumption toward the commodity causing pollution.
Keywords: 330